Analisis Kemiskinan Spasial dan Kaitannya dengan Sertifikasi dan Penggunaan Lahan Pertanian di Kabupaten Mamuju - Ade Irawadi; Bambang Juanda; Khursatul Munibah (TATALOKA, 2020)
The poverty is still a strategic issue in Mamuju Regency, West Sulawesi. In 2015 the poverty rate is 6.7%, but the decline of every year is still very slow. Understanding the relationship between poverty and the factors that influence it is important to determine the right policies for poverty alleviation in Mamuju Regency. This study aims to: (1) analyze spatial patterns of poverty; and (2) analyze the relationship of poverty with factors that influence spatially. This study used cross sectional village level data of 97 villages/kelurahan in the Mamuju Regency. The data used are poverty, land certification, agricultural land use, labor in industrial sector, distance to capital and village fund. A spatial analysis of poverty uses Moran Index approach to find out spatial pattern of poverty in Mamuju Regency. Analysis of the relationship between the poverty level of each village/kelurahan with the factors influence it using the Geographically Weighted Regression (GWR) approach. The result of spatial analysis of poverty indicates that the poverty level of the village/kelurahan in Mamuju Regency is clustered. The result of GWR analysis shows that the land certificates, the percentage of land area of plantation, paddy field, fields area, and fishpond, percentage of labor in micro and small industry sector, distance to the capital and village fund proved to have significant effect varying to village poverty level.